Irma Thompson, Mrs. Veronica D. Dengle, Gertrude T. Elliot, Esther F. Slack, Helen G. Shats, Jackson College freshman, 1933 - Munro, Melville S. (Tufts Archival Research Center, 2005)
Print is in Munro Collection, Box 055, p. 21, #10496